First Report of Neocosmospora Stem Rot of Soybean Caused by Fusarium neocosmosporiellum in Mississippi - Jimenez Madrid, Alejandra M (Plant disease, 2022)
In September 2021, diseased soybean [Glycine max (L.) Merr.] plants were observed in a commercial field in Lamar County, Mississippi (MS). Foliar symptoms included mild interveinal chlorosis and necrosis in the affected plants (Fig. 1a). Stems and roots exhibited orange to black lesions and pith discoloration (Fig. 1b). Signs of the fungus included orange-to-red spherical perithecia, observed in clusters on crowns and roots. Perithecia were surface-sterilized with 70% ethanol for 1 min. Subsequently they were gently pressed in a droplet of 5 μl of sterilized reverse osmosis (RO) water and the suspension was streaked onto potato dextrose agar (PDA) amended with chloramphenicol (75 mg/liter) and streptomycin sulfate (125 mg/liter). Plates were incubated in the dark at 25°C. White to light pink and floccose mycelia developed after four days of incubation and hyaline, one celled, cylindrical to oblong-ellipsoidal microconidia were observed (Fig. 2b; ×400). Conidia measured 8.8 to 19 × 2.8 to 5 μm (n=15). Abundant orange to brown perithecia developed on PDA after three weeks of incubation (Fig. 2a). The asci within the perithecia were cylindrical, eight-spored, thin walled and measured 94.6 to 123.6 μm × 10 to 14 μm (n=10). Ascospores were uniseriate, globose to ellipsoidal, hyaline to brown and measured 11.6 to 16 μm × 7 to 10 μm (n=10; Fig. 2c). The morphological characteristics were consistent with those of Fusarium neocosmosporiellum O'Donnell & Geiser (≅ Neocosmospora vasinfecta E. F. Sm.; Geiser et al. 2013). Genomic DNA was extracted from isolate TW068-21 from a 3-week-old culture plate. The internal transcribed spacer region (ITS), elongation factor 1-alpha (EF1-alpha) and calmodulin (cmdA) gene were amplified, and consensus sequences deposited in GenBank (OM640625, OM681343, OM681344). ITS and EF1-alpha sequence comparison using NCBI BLAST, showed > 99.2% similarity with N. vasinfecta JL2210 while cmdA sequence was 99.8% similar to strain CBS 517.71. A pathogenicity test was performed on 2-week-old Asgrow 46X6 soybean seedlings grown in 10.2 cm pots in a growth chamber. Isolate TW068-21 was grown on antibiotic-amended PDA for 4-weeks and inoculum suspension was prepared with sterilized RO water and adjusted to 2 × 105 ascospores/ml. Soybean seedlings (n=8) were removed from pots and roots were dipped into the inoculum suspension for 20 min. Four control plants were dipped in autoclaved RO water. Plants were re-planted in potting mix, and the inoculated plants were immediately drenched with 20 ml of the inoculum and placed in a growth chamber (25°C; 14 h light). The experiment was repeated once. Inoculated plants presented dark brown discoloration at the base of the stem after 3 weeks of incubation, but no foliar lesions were observed. Control plants remained asymptomatic. Symptomatic stems were placed in a moist chamber (≈23°C; 12 h:h light:dark) and light brown perithecia developed after 1 week. Fusarium neocosmosporiellum was re-isolated from perithecia and stems and colony and spore morphology were similar as described above. To our knowledge, this is the first report of F. neocosmosporiellum in MS. Signs and symptoms of this disease resemble red crown rot. Consequently, careful morphological and molecular assessments should be used for confirmation. Neocosmospora stem rot has been previously reported in Alabama (Gray et al. 1980), Arkansas (Greer et al. 2015), and Georgia (Phillips 1972). Yield losses due to this pathogen in MS are currently unknown